2020
DOI: 10.3389/fmed.2020.540929
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Exchange Arthroplasty for Fistulizing Periprosthetic Joint Infection of the Hip: An Effective Strategy

Abstract: Background: Prosthetic hip infection (PHI) is a disastrous scenario after an arthroplasty. International guidelines contraindicate one-stage exchange arthroplasty for fistulizing chronic prosthetic hip infection (FCPHI), nevertheless few surgical teams, mostly from Europe, support one stage procedure for this indication. Questions/Purposes: Analysis of infection recurrence and implant failure of a series of FCPHIs treated with one stage arthroplasty. Patients and Methods: Sixty-six FCPHIs treated with one-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
3
0
4
Order By: Relevance
“…Although we found a higher rate of polymicrobial infections (42%) than some studies (10% to 38% [30,31]), our results are similar to those reported by other authors (20,21,23), suggesting that our conclusions may apply in different settings (Tables 2 and 3). The higher-than-usual rate of polymicrobial OAI found in this study may be due to the specific recruitment in our setting, which is a large center for diabetic foot and polytrauma patients and patients with spine infections who are known to be likely to acquire polymicrobial infections (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 90%
“…Although we found a higher rate of polymicrobial infections (42%) than some studies (10% to 38% [30,31]), our results are similar to those reported by other authors (20,21,23), suggesting that our conclusions may apply in different settings (Tables 2 and 3). The higher-than-usual rate of polymicrobial OAI found in this study may be due to the specific recruitment in our setting, which is a large center for diabetic foot and polytrauma patients and patients with spine infections who are known to be likely to acquire polymicrobial infections (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 90%
“…Buchholz с соавторами [16], посвященной десятилетнему опыту одноэтапного реЭП, операция приобрела множество убежденных сторонников и противников. С тех пор опубликованы тематические метаанализы, отчеты о работе международных согласительных конференций, и острота дискуссии существенно уменьшилась, а в сообществе ортопедов формируется единый подход к выбору хирургической тактики [7,20,21]. Тем не менее не для всех проблем найдено очевидное решение.…”
Section: Discussionunclassified
“…S. Marmor с соавторами считают, что свищ не является препятствием к операции, если после его иссечения будет достаточно мягких тканей для первичного ушивания раны [9,21]. В исследовании A. Zahar с соавторами 10,6% больных имели один или несколько свищевых ходов, но у 94% из них не было рецидивов ППИ в течение 10 лет [9].…”
Section: Discussionunclassified
See 2 more Smart Citations